The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1111/1744-9987.12690
|View full text |Cite
|
Sign up to set email alerts
|

Critical Governance Issue of Parathyroid Hormone Assays and its Selection in the Management of Chronic Kidney Disease Mineral and Bone Disorders

Abstract: Measurement of circulating parathyroid hormone (PTH) levels is essential for optimal management of mineral and bone disorders (MBD) in chronic kidney disease (CKD) patients. There are two major types of PTH assays currently in use: intact parathyroid hormone (i-PTH) and whole PTH (w-PTH) assays. The i-PTH assay is the current standard, and considerable information regarding the management of CKD-MBD has been obtained with this method. However, several limitations have been found with the i-PTH assay. One limit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 64 publications
(74 reference statements)
0
7
0
Order By: Relevance
“…Kidney Disease Improving Global Outcomes (KDIGO) 2017 recommends routine parathyroid hormone, calcium, and phosphate checks on CKD patients starting from stage 3-5 to prevent or delay complications related to CKD [14]. KDIGO also suggests that MBD-PGK management should be based on serial measurements of parathyroid hormone serum and the tendency to persistently increase parathyroid hormone levels above the upper limit of normal value has more clinical significance than just one measurement [15]. Based on those mentioned above, this study aims to analyze the correlation between e-GFR and parathyroid hormone levels in predialysis CKD patients undergoing treatment at Sanglah General Hospital.…”
Section: Introductionmentioning
confidence: 99%
“…Kidney Disease Improving Global Outcomes (KDIGO) 2017 recommends routine parathyroid hormone, calcium, and phosphate checks on CKD patients starting from stage 3-5 to prevent or delay complications related to CKD [14]. KDIGO also suggests that MBD-PGK management should be based on serial measurements of parathyroid hormone serum and the tendency to persistently increase parathyroid hormone levels above the upper limit of normal value has more clinical significance than just one measurement [15]. Based on those mentioned above, this study aims to analyze the correlation between e-GFR and parathyroid hormone levels in predialysis CKD patients undergoing treatment at Sanglah General Hospital.…”
Section: Introductionmentioning
confidence: 99%
“…28 It should be stressed that routinely used second generation assay (iPTH) detects both (1-84)-PTH and (7-84)-PTH. 29 According to previous data, (7-84)-PTH accumulates progressively in the circulation along with eGFR decline, 30 therefore it may overestimate secondary hyperparathyroidism. Hence, iPTH assay may not sufficiently reflect PTHrelated VC and cardiovascular risk.…”
Section: Discussionmentioning
confidence: 98%
“…Like other C-PTH fragments, (7-84)PTH can be both degraded from (1-84)PTH in the liver and secreted by the parathyroid glands [13]. These fragments accumulate in the circulation of CKD patients and account for up to 45-50% of all circulating PTH molecular forms because they are mainly cleared through the kidney [14]. Previous studies have demonstrated that (7-84)PTH and C-PTH fragments increase as the estimated glomerular filtration rate (eGFR) decreases [15].…”
Section: Characteristics Of Pth Metabolismmentioning
confidence: 99%